Промоција на програмите за поддршка на земјоделскиот сектор во Европската унија и во Република Македонија - Оровчанец, Катерина (Економски факултет, УКИМ, Скопје, 2015)
The promotion of the programs for support in the agricultural sector is essential for the effective and efficient implementation of the policy for agricultural and rural development for the members of the European Union as well as for the candidate countries for EU accession and the potential candidate countries for EU accession. The promotion of the agricultural products from the European Union is one of the essential elements in the present globally increasing market. The Common Agricultural Policy represents a partnership between Europe and the farmers keeping in mind that agriculture is not merely food but is closely linked to the rural areas and the population residing in these areas. The policy for information and promotion of the agricultural products from the European Union represents one manner of complementation of the national programs for support of the agricultural sector reached by the member countries of the European Union and aims to enhance the competitiveness of agricultural products before European Union consumers and consumers in third countries, at the same time putting emphasis on the quality of the products, the safety of the products as well as the methods of production which contributes to the opening of new markets for the sale of the European Union products. In terms of active inclusion in the utilization of the European Union funds in the agricultural sector, the Republic of Macedonia undertakes series of measures and activities in terms of implementation of an appropriate legal regulations and institutional set up, in addition creating highly expert and professional staff all in the direction of improvement of the competitiveness of the Macedonian agricultural products on the international market.
Promotion of the support programmes for the agriculture sector in the European Union and in the Republic of Macedonia
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Нада Секуловска.
Keywords: promotion, information, competitiveness, programs, agriculture